The effect of destination image and personality towards destination choice: a study of Maldives - Haque, A. K. M. Ahasanul; Tarofde, Arun Kumar; Sheneen, Aishath; Uddin, Bashir; Sharif, Sultan Rahaman (Islamic Azad University (IAU), Iran, 2018)
Tourism is one of the utmost important industry in the Maldives. However, there is a little known about the important factors that affect destination choice, especially in the context of Maldives. Hence, the fundamental objective of this study is to examine crucial factors affecting destination choice. Based on the theory and extensive literature review, this study developed a conceptual model with two independent, one mediating and dependent variables. Five hypothesizes were developed and proposed to test. A cross-sectional and structured questionnaire based research design was applied and was able to collect from 220 international tourists in Maldives. Structural Equation Modelling was applied to test the hypothesis and results indicated that both, destination personality and choice has direct effect on both destination choices in the Maldivian context. Additionally, results also indicated that destination brand significantly mediate the relationship between independent and dependent variables. This study provides an in-depth understanding about the tourist destination choice behavior, which eventually helps this industry to develop destination brand and attract more international tourist in Maldives. Moreover, this study is one of the very few that investigate in the Maldives, which contribute new knowledge this context.